13.69=3.6x

Simple and best practice solution for 13.69=3.6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13.69=3.6x equation:



13.69=3.6x
We move all terms to the left:
13.69-(3.6x)=0
We add all the numbers together, and all the variables
-(+3.6x)+13.69=0
We get rid of parentheses
-3.6x+13.69=0
We move all terms containing x to the left, all other terms to the right
-3.6x=-13.69
x=-13.69/-3.6
x=3+2.89/3.6

See similar equations:

| 4(t+19)=4 | | 6(t+75)=-48 | | c+11/4=7 | | -52=t/5-57 | | r/7-18=-11 | | g-62/7=3 | | 5x-9=x+14 | | (3x-1)=(x-9) | | x/3.7=3.7/3.6 | | g/4=2.3 | | w/8-28=31 | | -4x-5=-18 | | x2+x6=-100 | | 62=7p-20 | | (x-2)(1.17)=0 | | -8(r-95)=8 | | 7Iy-5I=14 | | g/5-10=-5 | | u/4+-43=-45 | | 3s=65 | | 8=m-64/4 | | h+7/3=8 | | x^2-30x=80 | | 6n-36=15n-129 | | 1/2n-3+1/2n+1-1/n-1=0 | | 1=g/8-3 | | x^2-30x-80=0 | | 7n-4=31n | | 56x^2=56 | | 3m=14.4 | | 2x3-1=53 | | n+57/3=-4 |

Equations solver categories